When Freedom Becomes Another Prison: Reflections on Work, Attachment, and the Search for the DAO: English - Arga Abdi Rafiud Darajat Lubis (Argael Publisher, an imprint of CV. ARGA FARMA, 2026)
Freedom is a universal aspiration, yet its meaning changes with the life from which it is viewed. For some, freedom means financial independence and release from corporate schedules; for others, it means living without a spouse, children, social supervision, or obligations that dictate how time and money must be used. This perspective argues that every apparent liberation can generate another attachment. The employee may be bound to a corporation, while the entrepreneur becomes bound to a system of his own making, including payroll, clients, operating costs, ambition, and the fear of decline. The same paradox appears in family life, social expectations, religious accountability, and even the desire to be recognised as free. Human beings therefore seem to move not from bondage to absolute liberty, but from one form of attachment to another. From the author's perspective, freedom is the occasional capacity to do what one genuinely wishes without hesitation, obstruction, or submission to the judgement of others, while possessing the practical ability to act. Yet even this definition can become another prison when it is defended as an identity. The search for freedom may therefore culminate not in escape from life, but in finding a path - the Dao - through which one can move among obligations without being entirely possessed by them.